An Dealg sa bhFéar - Ní Dhomhnaill, Nuala,Nic Dhiarmada, Bríona,Bewick, Pauline (Cló lar-Chonnacht, 2011)
Irish poet, Nuala Ní Dhomhnaill's first two collections of poetry published under one cover.
Description based on publisher supplied metadata and other sources